A Matter of Relief Sanitary Conditions on Austrian Construction Sites - Bernroider, Katharina (My University, 2026)
Research on sanitary conditions on construction sites remains limited, and despite occupational health regulations, insufficient sanitary and hygiene conditions remain common on Austrian construction sites. Therefore, this study investigates why inappropriate hygiene conditions persist and identifies structural and cultural factors that hinder improvement. The study focuses on sanitary facilities and hygiene practices on Austrian construction sites, including toilets, handwashing facilities, and showers. Applying a qualitative and exploratory research design, data were collected through a visit to sites and semi-structured interviews with workers, management and regulatory actors. Furthermore, structural and cultural reasons for insufficient conditions were analysed using principal-agent theory and the safety culture theory. The key findings of the thesis include that while regulations are mostly sufficient, gender considerations as well as regulatory enforcement are weak. Furthermore, complex accountability structures and a cost focus complicate monitoring and communication, and few external incentives shift the quality of compliance and monitoring largely to intrinsic motivation. This is further complicated by poor hygiene conditions being culturally normalised and hygiene taking low priority in the health and safety context. The study demonstrates that adequate hygiene conditions are not yet embedded in the underlying assumptions of safety culture and require cultural change as well as structural improvements. These findings provide a foundation for future research and the practical improvements of hygiene conditions on Austrian construction sites.
Keywords: hygiene, sanitary facilities, construction, health and safety, Austria, principal-agent theory, safety culture